Behind the potential evolution towards prion resistant species. Issue 2 (4th March 2018) - Fernández-Borges, Natalia; Eraña, Hasier; Castilla, Joaquín
ABSTRACT: Historically, the observation of naturally occurring cases of prion disease led to the classification of different susceptibility grades and to the designation of prion resistant species. However, the development of highly efficient in vitro prion propagation systems and the generation of ad hoc transgenic models allowed determining that leporidae and equidae families have been erroneously considered resistant to prion infection. On the contrary, similar approaches revealed an unexpected high level of resistance of the canidae family. In PLoS Pathogens [1 ], we describe experiments directed toward elucidating which are the determinants of the alleged prion resistance of this family. Studies based on the sequence of the canine prion protein coupled with structural in silico analysis identified a key residue probably implicated in this resistance. Cell and brain-based PMCA highlighted that the presence of aspartic or glutamic acid at codon 163 of the canid PrP, strongly inhibits prion replication in vitro . Transgenic animals carrying this substitution in mouse PrP were resistant to prion infection after intracerebral challenge with different mouse prion strains. The confirmation of the importance of this substitution and its exclusivity in this family, suggests it could have been evolutionarily favored, due to their diet based on carrion and small ruminants.